Intergenerational Implications of Fiscal Consolidation in Japan - Tokuoka, Kiichi (IMF Working Papers; Working Paper ;, 2012)
In Japan, intergenerational inequality in lifetime resources is substantial, with a heavier fiscal burden on the young than the old. Moreover, given the need for fiscal consolidation, the inequality is even worse than existing policy would suggest. However, this does not mean that fiscal consolidation would make the young worse off. Lack of fiscal consolidation would eventually increase interest rates, which would reduce output and hit young generations harder. Simulations using an overlapping generations model indicate that, from the perspective of intergenerational fairness, it would be desirable to include both social security spending reforms and revenue measures in a fiscal consolidation package. The simulations also show that delaying fiscal consolidation could be costly and worsen intergenerational resource inequality.